Radiation creation of cation defects in alkali halide crystals: Review and today’s concept - Lushchik, A.; Lushchik, Ch.; Vasil’chenko, E.; Popov, A.I. (Физика низких температур, 2018)
Irradiation of alkali halide crystals creates pairs of Frenkel defects both in anion and cation sublattices. How-ever, the particular nonimpact creation mechanisms (related to the decay of different electronic excitations) of cation Frenkel pairs are still unclear. At helium temperatures, there is yet no direct evidences of the creation of stable (long-lived) elemental cation defects. On the other hand, a number of complex structural defects containing cation vacancies and/or interstitials, were detected after irradiation of alkali halides at higher temperatures. Besides already proved mechanism related to the association of H and VK centers into trihalide molecules, the following possibilities of cation interstitial-vacancy pair creation are analyzed as well: (i) a direct decay of cation or anion excitons, (ii) the transformation of anion Frenkel pairs, formed at the decay of anion excitons or e-h recombination, into cation ones.